Hierarchical Framework for Determining E-Commerce Platforms for SMEs: AHP Approach Based on Marketing and Operational Perspectives - Nova Riandi; Muhammad Farhan (International Journal Business and Entrepreneurship, 2026)
The rapid growth of digital commerce has created new opportunities for small and medium-sized enterprises (SMEs) to expand market reach and improve business efficiency through e-commerce platforms. However, the increasing number of available platforms makes the selection process more complex, as each platform offers different marketing and operational features. This study aims to develop a hierarchical decision-making framework to determine the most suitable e-commerce platform for SMEs by integrating marketing and operational perspectives. The research applies the Analytic Hierarchy Process (AHP) to evaluate multiple criteria and rank alternative platforms. The evaluation framework consists of two main perspectives—marketing and operational—with twelve sub-criteria derived from the literature on digital platforms and SME digitalization. Data were collected through expert judgments using pairwise comparison questionnaires and analyzed using the AHP method to determine criteria weights and platform priorities. The results show that the marketing perspective has a higher priority weight than the operational perspective, indicating that SMEs prioritize market reach, promotional tools, and customer engagement when selecting platforms. The final ranking reveals that Shopee is the most suitable platform for SMEs, followed by Tokopedia, TikTok Shop, and Lazada. This study provides a structured decision-support framework that can help SMEs evaluate and select e-commerce platforms more systematically.